2008
DOI: 10.1007/s00134-008-1176-7
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric acute kidney injury in the ICU: an independent evaluation of pRIFLE criteria

Abstract: We observed a high incidence of significant AKI in a PICU population at risk, which was associated with high mortality. Pediatric RIFLE criteria may guide in the early identification of patients at risk for AKI and in the initiation of therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
147
3
5

Year Published

2010
2010
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 184 publications
(158 citation statements)
references
References 11 publications
3
147
3
5
Order By: Relevance
“…Similarly, in the Plötz et al (26) study, 45% of the patients were diagnosed AKI in their first 24 hours. Akcan-Arikan et al (23) identified AKI in 42.3% of their sample.…”
Section: Discussionmentioning
confidence: 74%
See 4 more Smart Citations
“…Similarly, in the Plötz et al (26) study, 45% of the patients were diagnosed AKI in their first 24 hours. Akcan-Arikan et al (23) identified AKI in 42.3% of their sample.…”
Section: Discussionmentioning
confidence: 74%
“…Regarding the AKI level, the maximal RIFLE score found during the patients stay was 39.1% R, 39.1% I and 21.8 F, while Akcan-Arikan et al (23) found 48.8%, 26% and 25.2%, respectively, and Plötz et al (26) 52%, 37% and 11%, respectively.…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations